Digital Health Readiness, Leadership Agility, and Interprofessional Collaboration as Drivers of Hospital Innovation Performance - M Rizki Herwindo; Liman Julianto Siauw; Fransiskus Sidartha Wijaya; Gleneges Octaverina Siregar (LPPM Universitas Buddhi Dharma, 2026)
This study aims to analyze the influence of Digital Health Readiness, Interprofessional Collaboration, and Leadership Agility on Hospital Innovation Performance in hospitals. Data were collected from 202 hospital staff using a structured questionnaire. Analysis was conducted using the PLS-SEM approach to test the direct effects, total effects, and constructual performance of each variable. The results showed that Leadership Agility had the most dominant and significant influence on hospital innovation performance, emphasizing the importance of adaptive leadership, responsiveness to change, and the ability to lead teams effectively. Interprofessional Collaboration also contributed positively and significantly, indicating that cross-professional coordination and cooperation enhance innovation effectiveness through team synergy and collective decision-making. Conversely, Digital Health Readiness did not show a significant influence on innovation performance, despite its relatively high constructual performance, indicating that digital readiness needs to be optimized through more mature technology implementation and utilization strategies. These findings confirm that the success of hospital innovation depends heavily on the combination of agile leadership, effective professional collaboration, and strategic use of digital technology. The results of this study are expected to serve as a basis for developing managerial strategies and increasing hospital innovation capacity in the era of digital transformation.